Fullerene C60 Protects Against Intestinal Injury from Deoxynivalenol Toxicity by Improving Antioxidant Capacity - Simeng Liao; Guang Liu; Bie Tan; Ming Qi; Jianjun Li; Xiaoqing Li; Changfeng Zhu; Jiamei Huang; Yulong Yin; Yulong Tang (Life, 2021)
Oxidative stress is involved in a wide variety of pathologies, and fullerene has been shown to have an antioxidant ability. Mycotoxins exert toxic effects through induction of excessive reactive oxygen species (ROS). Here, we evaluated water-soluble fullerene C60 for its anti-mycotoxin and antioxidant effects in vitro and in vivo. Intestinal epithelial cells were cultured with fullerene during deoxynivalenol (DON) exposure. The results revealed that fullerene C60 significantly promoted cell viability, decreased apoptosis and necrotic cell number, and significantly reduced intracellular ROS levels during DON exposure (p < 0.05). To investigate the role of fullerene in antioxidant capacity in vivo further, 40 three-week-old male C57BL/6 mice were randomly divided into four groups. There were no significant differences between the control and fullerene groups (p > 0.05). In mice exposed to DON, supplementation with fullerene C60 significantly improved growth performance, and enhanced the total antioxidant status and the activities of SOD and GPX in the intestine and liver (p < 0.05). In addition, fullerene C60 supplementation improved intestinal morphology, as indicated by a higher villus height and tight junction protein expression (p < 0.05). Furthermore, fullerene supplementation decreased serum concentrations of inflammatory cytokine and lipopolysaccharide (LPS; a penetrability marker) compared to the DON-challenged group (p < 0.05). The current study suggests that fullerene C60 improves intestinal antioxidant status against DON-induced oxidative stress in vitro and in vivo.